The epithelial-to-mesenchymal transition activator ZEB1 initiates a prometastatic competing endogenous RNA network - Tan, Xiaochao (J Clin Invest, 2018)
Epithelial tumor cells undergo epithelial-to-mesenchymal transition (EMT) to gain metastatic activity. Competing endogenous RNAs (ceRNAs) have binding sites for a common set of microRNAs (miRs) and regulate each other’s expression by sponging miRs. Here, we address whether ceRNAs govern metastasis driven by the EMT-activating transcription factor ZEB1. High miR-181b levels were correlated with an improved prognosis in human lung adenocarcinomas, and metastatic tumor cell lines derived from a murine lung adenocarcinoma model in which metastasis is ZEB1-driven were enriched in miR-181b targets. ZEB1 relieved a strong basal repression of α(1) integrin (ITGA1) mRNA, which in turn upregulated adenylyl cyclase 9 mRNA (ADCY9) by sponging miR181b. Ectopic expression of the ITGA1 3′-untranslated region reversed miR-181b–mediated metastasis suppression and increased the levels of adenylyl cyclase 9 protein (AC9), which promoted tumor cell migration and metastasis. In human lung adenocarcinomas, ITGA1 and ADCY9 levels were positively correlated, and an AC9-activated transcriptomic signature had poor-prognostic value. Thus, ZEB1 initiates a miR-181b–regulated ceRNA network to drive metastasis.